African Development Indicators 2005 - World Bank (Washington, DC, 2013)
As in previous years, African Development Indicators (ADI 2005 assembles economic, social, and environmental data from a variety of sources to present a broad picture of development across Africa. Some of the key improvements in this year's edition are the reduction of macroeconomic and other data lags, enabling external debt reporting up to 2003 and updates on the HIPC initiative. This volume presents the available relevant data for 1980-2003, grouped into 17 chapters: background data; national accounts; prices and exchange rates; money and banking; external sector; external debt and related flows; government finance; agriculture; power, communications, and transportation; doing business; labor force and employment; aid flows; social indicators; environmental indicators; HIPC; household surveys; and public enterprises. Chapter 14 (environmental indicators) was once again taken from the World Resources Institute's World Resources 2002-2004: Decisions for Earth: Balance, Voice and Power, which is a repeat from ADI 2004. Each chapter begins with a brief introduction on the nature of the data, followed by a set of charts, statistical tables, and technical notes. These notes define the indicators and identify specific sources. Most macroeconomic data (in particular, national accounts, balance of payments, government finance statistics, and trade) reflect data maintained by World Bank country desks, often referred to as operational data. These data are often more up to date and offer better country coverage than the data stored in the Bank's central files, the Statistical Information Management and Analysis Database (SIMA),